Analysis of industrial-scale high-temperature combined sensible/latent thermal energy storage. (25th May 2016) - Geissbühler, L.; Kolman, M.; Zanganeh, G.; Haselbacher, A.; Steinfeld, A.
Abstract: An experimental-numerical approach was used to study combined sensible/latent heat storage based on placing a limited amount of steel-encapsulated AlSi12 on top of a packed bed of rocks. The primary motivation for combining sensible and latent heat storage is to reduce the drop in outflow temperature during discharging that can be observed for sensible heat storage. An unsteady one-dimensional heat-transfer model was verified using exact solutions and validated with experimental data from a 42 kWhth laboratory-scale combined storage. Simulations were then used to compare the performance of 23 MWhth and 1000 MWhth industrial-scale combined and sensible storages. The simulations showed that the combined storage can reduce the material costs for a given maximum outflow temperature drop during discharging. The simulations also demonstrated that the industrial-scale combined storages meet the goals of the U.S. Department of Energy's SunShot Initiative of exergy efficiencies greater than 95% and material costs below 15/kWhth .